Transmembrane TM3b of Mechanosensitive Channel MscS Interacts With Cytoplasmic Domain Cyto-Helix - Wang, Xiaomin; Tang, Siyang; Wen, Xiaoxu; Hong, Lang; Hong, Feifan; Li, Yuezhou (Frontiers in Physiology, 2018)
The mechanosensitive channel MscS functions as an osmolyte emergency release-valve in the event of a sudden decrease in external environmental osmolarity. MscS has served as a paradigm for studying how channel proteins detect and respond to mechanical stimuli. However, the inter-domain interactions and structural rearrangements that occur in the MscS gating process remain largely unknown. Here, we determined the interactions between the transmembrane domain and cytoplasmic domain of MscS. Using in vivo cellular viability, single-channel electrophysiological recording, and cysteine disulfide trapping, we demonstrated that N117 of the TM3b helix and N167 of the Cyto-helix are critical residues that function at the TM3b-Cyto helix interface. In vivo downshock assays showed that double cysteinesubstitution at N117 and N167 failed to rescue the osmotic-lysis phenotype of cells in acute osmotic downshock. Single-channel recordings demonstrated that cysteine cross-linking of N117C and N167C led to a non-conductive channel. Consistently, coordination of the histidines of N117H and N167H caused a decrease in channel gating. Moreover, cross-linked N117 and N167 altered the gating of the severe gain-of-function mutant L109S. Our results demonstrate that N117-N167 interactions stabilize the inactivation state by an association of TM3b segments with β-domains of the cytoplasmic region, providing further insights into the gating mechanism of the MscS channel.